2022
DOI: 10.3389/fped.2022.955339
|View full text |Cite
|
Sign up to set email alerts
|

Predicting South Korean adolescents vulnerable to obesity after the COVID-19 pandemic using categorical boosting and shapley additive explanation values: A population-based cross-sectional survey

Abstract: ObjectiveThis study identified factors related to adolescent obesity during the COVID-19 pandemic by using machine learning techniques and developed a model for predicting high-risk obesity groups among South Korean adolescents based on the result.Materials and methodsThis study analyzed 50,858 subjects (male: 26,535 subjects, and female: 24,323 subjects) between 12 and 18 years old. Outcome variables were classified into two classes (normal or obesity) based on body mass index (BMI). The explanatory variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Quality was assessed using the modified Newcastle–Ottawa Scale [ 19 ]. Out of included forty studies, 16 were classified as good quality [ 26 , 27 , 33 38 , 45 , 46 , 48 , 49 , 54 , 58 , 59 ] while twenty-four were also classified as satisfied [ 21 25 , 28 31 , 39 44 , 47 , 50 53 , 55 – 57 , 60 ]. Twenty-four articles were done on the adult population [ 22 , 23 , 25 , 26 , 28 30 , 36 , 38 , 42 44 , 46 , 48 50 , 55 , 57 59 ], five articles were done only adolescents [ 31 , 39 , 41 , 47 , 60 ], three research articles were also done on children [ 34 , 53 , 54 ], and finally, eight articles were done on both children and adolescents [ 21 , 24 , 27 , 33 , 37 , 45 , 52 , 56 ] as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Quality was assessed using the modified Newcastle–Ottawa Scale [ 19 ]. Out of included forty studies, 16 were classified as good quality [ 26 , 27 , 33 38 , 45 , 46 , 48 , 49 , 54 , 58 , 59 ] while twenty-four were also classified as satisfied [ 21 25 , 28 31 , 39 44 , 47 , 50 53 , 55 – 57 , 60 ]. Twenty-four articles were done on the adult population [ 22 , 23 , 25 , 26 , 28 30 , 36 , 38 , 42 44 , 46 , 48 50 , 55 , 57 59 ], five articles were done only adolescents [ 31 , 39 , 41 , 47 , 60 ], three research articles were also done on children [ 34 , 53 , 54 ], and finally, eight articles were done on both children and adolescents [ 21 , 24 , 27 , 33 , 37 , 45 , 52 , 56 ] as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All the included studies revealed body weight changes during the pandemic. The mean weight gain during COVID-19 pandemic ranged from 0.04 (SD = 1.18) [ 42 ] to 2.8 (SD = 3.7) [ 37 ] and the prevalence of weight gain ranged from 17.9% [ 47 ] to 52.2% [ 42 ]. Despite this, some studies reported that the determinants of weight gain decreased during the COVID-19 lockdown [ 28 , 29 , 44 , 46 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations